A política nacional dos refugiados e os impactos sociais da inserção destes no estado do Rio Grande do Sul a partir do século XXI - (:unkn) unknown (Universidade Federal do Pampa, 2016)
This study aims to present the International Protection System for Refugees through a historical background to the creation of some basic rights to human beings such as the International Human Rights Law, International Humanitarian Law and International Law to Refugees. Even with their specificities, these rights often work together seeking to assimilate their affinities according to the cause. To be treated the international media as the 1951 Convention and its 1967 Protocol, as well as at the regional level with the Declaration of Cartagena and the Brazilian Refuge Act, seeks to elucidate how comprehensive are these protective measures to forcibly displaced. The need to address in Chapter 2 the State of Brazil and its Federal Constitution of 1988 as well, the Law 9.474 / 97, to present the forms that are internally developed integration work with partner institutions. Then, in Chapter 3 will be presented to the protective measures and affirmative action, which developed in Rio Grande do Sul state with partner institutions. These social activities are developed to better inclusion and integration of migrants, forcibly displaced and stateless persons.
Keywords: International relations: Brazil; International human rights law; Migration; Refugees; Relações internacionais: Brasil; Direito internacional; Migração; Refugiados; CNPQ::CIENCIAS SOCIAIS APLICADAS